Capacidad antioxidante y aceptabilidad de una bebida tipo néctar con extractos vegetales, pulpa de pitahaya y maracuyá - Mejía Zambrano, María Antonia (2024)
This research aimed to evaluate the antioxidant capacity and sensory acceptability of a nectar-like beverage with plant extracts, pitahaya pulp, and passion fruit, in order to examine the bioactive components in the beverage. Chemical analyses of pH, antioxidant capacity using the ABTS method, and sensory analysis via a five-level Likert scale were performed. A Simplex-Lattice mixture design was applied to the components (plant extracts), obtained using ultrasound equipment, from three plant materials (plantain, oregano, and zorrilla) with a maximum proportion of 3%, generating 14 runs. The pulp content was consistent across all treatments, in a 1:3 ratio, where one part consisted of passion fruit pulp (25%) and three parts of pitahaya pulp (75%). Subsequently, pH analysis showed that all beverage treatments were within the range established by NTE INEN 2337, 2008 (pH less than 4.5). Additionally, in terms of antioxidant capacity, Treatment T12 (0.5% plantain, 2% oregano, and 0.5% zorrilla) had the highest value at 302.7054 µmol Trolox Equivalent/mL, indicating no significant differences among the treatments in the evaluated variables. Sensory analysis statistically confirmed that the treatments did not differ from one another in the evaluated attributes, meaning that the tasters did not perceive differences between treatments. In conclusion, the studied factors did not present significant effects, as the selected spatial cubic model did not predict behavior in relation to the dependent variables of pH, antioxidant capacity, and sensory analysis.